The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1017/s0144686x21000519
|View full text |Cite
|
Sign up to set email alerts
|

Increasing autonomy through improved care: effects of a professional care-giver training programme on the functional status of older adults

Abstract: The aim of the present research was to evaluate the effectiveness of a care-giver training programme that trains professional care-givers in cognitive stimulation strategies for functional maintenance in care-dependent older adults. The sample contained 69 older adults (37 in the treatment group, 32 control group) assessed with the Barthel Index, the Mini-Mental State Examination and the Clifton Assessment Procedure for the Elderly (Cognitive Scale). Participants in the treatment group were treated by professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In line with this result lt, a study from (Navarro et al, 2021), by using module training and SSFQ (Star Staf Feedback Quessionaire) showed that caregivers in the treatment group believed the program modules were useful, giving it a mean score of 4.86 (SD = 0.378) on an ordinal scale of 0 to 5 and mentioning that their participation in the program had been a very positive experience and had contributed to increasing their professional knowledge, satisfaction and confidence.…”
Section: Support From Caregiversmentioning
confidence: 72%
“…In line with this result lt, a study from (Navarro et al, 2021), by using module training and SSFQ (Star Staf Feedback Quessionaire) showed that caregivers in the treatment group believed the program modules were useful, giving it a mean score of 4.86 (SD = 0.378) on an ordinal scale of 0 to 5 and mentioning that their participation in the program had been a very positive experience and had contributed to increasing their professional knowledge, satisfaction and confidence.…”
Section: Support From Caregiversmentioning
confidence: 72%
“…Based on the foregoing, prior studies using experimental and control groups have verified significant improvement in the cognitive functioning, motor execution and visuomotor coordination, and functional ability of older adults in the care of professional caregivers trained in a programme of cognitive intervention strategies that were incorporated into their usual caregiving tasks (Navarro et al, 2021;Sanjuán et al, 2018).…”
Section: What Does This Paper Contribute To the Wider Global Community?mentioning
confidence: 98%